HAMBATAN DALAM MEWUJUDKAN HUBUNGAN KONSELING - Maulana, Pu’ad; Karneli, Yeni; Mudjiran, Mudjiran (Program Studi Bimbingan Konseling Islam, Fakultas Tarbiyah Dan Ilmu Keguruan, Institut Ummul Quro Al-Islami Bogor, 2024)
The counseling relationship is a key element in an effective counseling process. This relationship is characterized by trust, empathy, and open communication between the counselor and the client. However, in practice, there are various barriers that can interfere with the realization of an optimal counseling relationship. This study aims to identify the main barriers in building a counseling relationship and explore strategies to overcome them. The identified barriers include internal client factors, such as distrust, fear of stigma, and difficulty in expressing emotions; and external factors, such as lack of counselor competence, cultural differences, and an unsupportive counseling environment. In addition, interpersonal dynamics such as perceptual bias and value conflicts can also affect the quality of the counseling relationship. The results of the study indicate that an empathy-based approach, effective communication, and cultural awareness can help reduce these barriers. This abstract provides insights for counselors to improve the effectiveness of counseling practice by strengthening inclusive and supportive counseling relationships